Thermal Energy Evaluation of Biomass Heating System - V. P. Khambalkar; S. R. Kalbande (International Journal of Engineering and Management Research, 2019)
The drying capacity of the system, fuel and air required for the drying was estimated. Based on the quantification of fuel and air required in the drying application, the dryer surface area and combustor furnace size were computed. The net heat duty of the heat exchanger for the parallel flow type exchanger was estimated in the experimentation. The exchanger design parameters were computed for the LMTD, net heat transfer area, number of tubes and diameter, and heat transfer coefficient was determined in the study. The system was developed as per the design specification in respect of each component. The biomass-based air heating system consisted of biomass combustor equipped with pre-heating arrangement and smoke tapping unit, air distribution system and rotary tray drying bin. The power transmission system was designed and developed for rotating tray arrangement for the live and static load during the operation. The thermal energy performance of the system was worked out during the experimentation for drying of green gram for the set operational parameters like air flow rate, temperature and fuel feed rate for the various combination of treatment. In investigation, the heat supplied by the combustor in various treatments for the set air flow rate, temperature and fuel feed rate is estimated in drying application. The heat gain by air, heat supplied to the drying bin, net heat utilized in the various treatments is estimated. The loss of heat from the combustor, in air distribution system and total system heat loss is computed in the experimentation for drying application. The component wise heat loss was estimated during the operation for the treatments. The overall energy balance for the drying was examined during the study.